Analysis of the Impact of Continuous Ambulatory Peritoneal Dialysis on Nutritional Status in Pediatric Chronic Kidney Disease - Putri Amirah; Henny Adriani Puspitasari; Cut Nurul Hafifah (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Chronic kidney disease (CKD) is a serious problem for all age groups, particularly in children. Several studies have shown that patients with CKD who underwent dialysis, including Continuous Ambulatory Peritoneal Dialysis (CAPD), experienced malnutrition, short stature and growth retardation. This study aimed to evaluate the correlation between the indicators of CAPD regiments with the nutritional status of pediatric patients with CKD and factors that influence it. Method: We conducted a cross-sectional study by collecting secondary data from medical records such as disease stage and duration, the most recent CAPD regimen, etiology, and comorbidities. Data on nutritional status was then obtained by measuring body weight, height, and upper arm circumference. The measurement was then plotted using the WHO anthropometry application or the CDC growth chart. Demographic data such as the education level of father and mother, family economic status, age, and gender were obtained by filling out the Case Report Form (CRF). Result: A total of fifteen respondents were included in this study. Children with CKD who underwent CAPD primarily had normal nutritional status with very short stature. Furthermore, no significant association was found between the CAPD regiments with the nutritional status of children with chronic kidney disease who are undergoing CAPD (p>0.05). Conclusion: Children with CKD who underwent CAPD primarily had normal nutritional status with very short stature. There was no correlation between the parameters of CAPD regiments with the nutritional status of CKD patients who underwent CAPD. This indicates that the regiment used in this study is already quite satisfactory as it does not impact the nutritional status of those patients.